BRIDGING MULTICULTURAL COMMUNICATION COMPETENCE AND COMMUNICATION APPREHENSION: A UNIVERSITY FOREIGN LANGUAGE LEARNERS’ EXPERIENCES - Fikroni, Moh. Rofid (International Journal of Instructions and Language Studies, 2025)
In an increasingly globalized world, the ability to communicate effectively across cultures is vital, particularly for English Foreign Language (EFL) learners navigating diverse communicative contexts. To be able to communicate effectively, one should have proper multicultural awareness-based competence. This study investigates the relationship between university-level EFL students Multicultural Communication Competence (MCC) and their Communication Apprehension (CA). Drawing on a sample of 120 learners, the study employs quantitative methods, including descriptive statistics and Pearson correlation analysis, to examine how cognitive, affective, and behavioral dimensions of MCC relate to various forms of CA, such as interpersonal, group, public speaking, and meeting-related anxiety. The results reveal a significant negative correlation between MCC and CA in which it suggests that students with higher multicultural awareness and adaptive communication behaviors are less likely to experience anxiety in cross-cultural interactions. The study underscores the need to integrate intercultural competence training into EFL curricula to reduce communicative barriers and foster greater linguistic and cultural confidence. Implications for pedagogy and future research directions are discussed